INTEGRATION OF AUGMENTED REALITY (AR) TECHNOLOGY IN ENGLISH SPEAKING LEARNING - Anggraini, Lesi; Apriana (Esteem Journal of English Education Study Programme, 2025)
This study investigates the effectiveness of Augmented Reality (AR) in improving students’ English speaking skills. Employing a quasi-experimental design with a pre-test and post-test control group, the research involved 60 eleventh-grade students at SMA Negeri 3 Pagaralam, divided into experimental and control groups. The experimental group received speaking instruction integrated with AR, while the control group followed conventional methods. Data were collected through speaking tests, questionnaires, and observation sheets. The results show a significant improvement in the experimental group’s speaking performance, with a mean gain of 9.52 points, compared to 3.9 points in the control group. The paired sample t-test confirmed a significant difference (p < 0.05) in the experimental group’s pre- and post-test scores. Moreover, the independent t-test indicated a significant difference in post-test results between both groups. Questionnaire analysis revealed that students responded positively to AR-based learning, noting increased motivation, enjoyment, and confidence. These findings suggest that AR is an effective tool for enhancing speaking skills by providing interactive, contextual, and immersive learning experiences. The study recommends further exploration of AR in other language skills and diverse classroom contexts.